Crime scene processing a multimedia crime scene training program - LaForte, Michael F.; Knox, Michael A. (Glen St. Mary, FL : Eagle Crime Scenes, Inc. ; New York : Distributed by Insight Media, 2007)
"This interactive, multimedia ebook contains 23 lessons of information about every aspect of crime scene investigations to include legal issues; courtroom readiness; searching for, documenting, and collecting evidence; crime scene photography; diagramming; developing latent fingerprints; obtaining DNA evidence; reconstructing crime scene events; and much, much, more."
This disc is a recorded DVD and may fail to play on some DVD equipment.
Includes index.
DVD-R.
System requirements: Microsoft Windows-based PC, DVD-ROM, Microsoft Internet Explorer 7, Adobe Flash plug-in, Adobe Acrobat reader.
Keywords: Evidence, Criminal -- Handbooks, manuals, etc; Forensic sciences -- Handbooks, manuals, etc; Criminal investigation -- Handbooks, manuals, etc